Behaviour of clayey soils under slow repeated loading and laboratory estimation of K(0) for overconsolidated sands. - Abdi, Hadj. (University of Ottawa (Canada), 1994)
Repeated undrained load tests were carried out under the application of cyclic deviator stresses at a frequency that varies from 0.0001 Hz up to 0.001 Hz. For a specific amplitude of applied stress, a critical level of repeated loading (CLRL) was evaluated for both kaolinite and crust clays. The strength of the soil is affected by the frequency, cyclic fluctuation of water table, and the amount of axial strain developed during cycling. The decrease in postcyclic strength is strain-dependent. It is further shown that cycling below the CLRL causes an increase in the overconsolidation of the clayey soils. The effect of cycling in behaviour of soils increases with increasing the OCR. This thesis also describes a method for the determination of in situ horizontal stresses of heavily overconsolidated sands using a stress-path triaxial apparatus. This method was proposed by Garga and Khan (1991) who applied it for overconsolidated clays. The proposed method is based on the concept that if the radial stress exceeds the in situ horizontal stress, while maintaining the axial stress constant and equal to the in situ vertical effective stress, only then will the sample experience significant axial strain. In this investigation, the above method is applied to the samples of known stress histories of overconsolidated sand. The effect of the complex stress history undergone by soils on the estimation of K$\sb0$ by the proposed method is investigated in laboratory. It is found that the proposed method replicated the imposed "in situ" horizontal stress exactly. Also this method is capable of estimating $\rm K\sb0$ of an overconsolidated soil irrespective of the previously imposed stress history. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.